Pelatihan Kader Anti Hipertensi di RW 15, Kelurahan Penjaringan, Jakarta Utara - Nur Fitriah; Regina Satya; Felicia Kurniawan; Bryany Titi Santi (Jurnal Pengabdian Pada Masyarakat, 2021)
TRAINING OF ANTY-HYPERTENSION CADRES IN RW 15, PENJARINGAN, NORTH JAKARTA. The prevalence of NCD Non-Communicable Diseases (NCD) in Indonesia is increasing, including hypertension. DKI Jakarta is one of the provinces with high prevalence of hypertension. To prevent complications due hypertension, regular screening and monitoring of risk factors is needed. Screening and monitoring of risk factors have been carried out by health officers through Posbindu PTM, also the active role of the community is needed. RW 15 Penjaringan is one of the RW with high prevalence of hypertension (29.9%) even though they already have Posbindu. The problems that occur in their Posbindu are the low number of visits by people with hypertension, the cadres lacks of knowledge about hypertension, lack of skills in measuring blood pressure, and lack of tensimeter to cover people with hypertension. To overcome this problem, RW 15 runs an anti-hypertension program that requires active and skilled cadres. It is necessary to train cadres for the sustainability of the program. These cadre training includes a pre-post test to measure cadres' knowledge, provide education about hypertension, then demonstrations and simulations of blood pressure measurement. After that, the cadres' knowledge of hypertension increased, and all cadres were able to measure blood pressure using a tensimeter. It is hoped that when the program run, cadres will be able to apply what was done during the training properly, and material refreshment should be done to maintain the quality of cadres’ knowledge.